CD40 ligand blockade induces CD4+ T cell tolerance and linked suppression. - Honey, K; Cobbold, S; Waldmann, H (1999)
The CD40-CD40 ligand (CD40L) interaction is a key event in the initiation of an adaptive immune response, and as such the therapeutic value of CD40L blockade has been studied in many experimental models of tissue transplantation and autoimmune disease. In rodents, transplantation of allogeneic tissues under the cover of anti-CD40L Abs has resulted in prolonged graft survival but not tolerance. In this report, we show that failure to induce tolerance probably results from the inability of anti-CD40L Abs to prevent graft rejection elicited by the CD8+ T cell subset. When the CD8+ T cell population is controlled independently, using anti-CD8 Abs, then tolerance is possible. Transplantation tolerance induced by anti-CD4 mAbs can often be associated with dominant regulation, manifested as infectious tolerance and linked suppression, both of which are mediated by CD4+ T cells. We show here that CD4+ T cells rendered tolerant using anti-CD40L therapy exhibit the same regulatory property of linked suppression, as demonstrated by their ability to accept grafts expressing third party Ags only if they are expressed in conjunction with the tolerated Ags. This observation of linked suppression reveals a hitherto undocumented consequence of CD40L blockade that suggests the tolerant state is maintained by a dominant regulatory mechanism. Our results suggest that, although anti-CD40L Abs are attractive clinical immunotherapeutic agents, additional therapies to control aggressive CD8+ T cell responses may be required.